How to solve a cubic equation

Consider the general cubic equation



y = x + \omega \implies x = y - \omega.\quad\quad\quad(1)

Substituting (1) into (*), we have

(y-\omega)^3 + b(y-\omega)^2+c(y-\omega) + d = 0.

This is a new cubic equation in y:

y^3 + (b-3\omega)y^2 + (3\omega^2-2b\omega+c)y - \omega^3+b\omega^2-c\omega+d=0\quad\quad\quad(2)


\omega = \frac{b}{3}\quad\quad\quad(3)

so that (2) becomes

y^3 + (c-\frac{b^2}{3})y+d-\frac{bc}{3}+\frac{2b^3}{27}=0.

That is


where p = c-\frac{b^2}{3}, q = -d+\frac{bc}{3}-\frac{2b^3}{27} (see Fig. 1).

Thus, (4) is the so called depressed cubic equation. A solution is readily available through Cardano’s formula (see “Through the Mind’s Eye“).

Once we know y, (1) gives

x = y - \frac{b}{3}.

Fig. 1

One thought on “How to solve a cubic equation

  1. Pingback: How to solve a quartic equation |

Leave a Reply

Fill in your details below or click an icon to log in: Logo

You are commenting using your account. Log Out /  Change )

Google photo

You are commenting using your Google account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s